Perancangan Sudu Turbine Expander Menggunakan Profil NACA 0018 Dengan Program Cascade dan CFD - I Marlon Managi (Universitas Ngeri Malang, 2023)
Research and development of the Organic Rankine Cycle (ORC) is becoming increasingly intense for converting heat into electricity. Many heat sources are available such as: solar radiation, biomass combustion, heat waste from factory and geothermal. Radial turbine is chosen for Organic Rankine Cycle due to its simple structure, components availability, and ease of application on a small power plant scale. The efficiency of the cycle is highly dependent on the design of the radial turbine. This study aims to obtain a turboexpander design with the utilization of NACA0018 airfoil as a stator. Optimization of stator blade with direct analysis method using